Awareness and Use of OER by Higher Education Students and Educators within the Graphic Arts Discipline in Greece - Alexandra Christoforidou; Elissavet Georgiadou (MDPI AG, 2021)
In recent years, Open Educational Resources (OER) have gained significant reach globally as a means of facilitating free and open access to educational materials. However, most of the empirical research on the adoption of OER in higher education is conducted in the US, while Europe and other countries, including Greece, fall behind. To that end, this research focused on the awareness and use of OER by higher education students and educators within the Graphic Arts discipline in Greece, to provide evidence regarding the adoption of OER to university administrations and libraries and encouraging their use across campus. The findings suggest that awareness is low, especially among undergraduate students, despite the fact that educators are aware of OER and already share their work as such. This paradox is probably related to students' vague knowledge of what OER are and how to use them for learning. Therefore, actions are required from educators, university administration and librarians to inform students of the benefits of OER adoption in the educational process as well as to communicate educators' OER efforts to students. Moreover, participants identified as the biggest obstacle for adopting OER in Graphic Arts the lack of a portal that accommodates OER for this discipline, which lays the groundwork for further research.